Google and the digital divide : the bias of online knowledge - Segev, Elad (Chandos internet series, 2010)
Aimed at information and communication professionals, scholars and students, Google and the Digital Divide: The Biases of Online Knowledge provides invaluable insight into the significant role that search engines play in growing the digital divide between individuals, organizations, and states. With a specific focus on Google, author Elad Segev explains the concept of the digital divide and the effects that today's online environment has on knowledge bias, power, and control. Using innovative methods and research approaches, Segev compares the popular search queries in Google and Yahoo in the United States and other countries and analyzes the various biases in Google News and Google Earth. Google and the Digital Divide shows the many ways in which users manipulate Google's information across different countries, as well as dataset and classification systems, economic and political value indexes, specific search indexes, locality of use indexes, and much more. Segev presents important new social and political perspectives to illustrate the challenges brought about by search engines, and explains the resultant political, communicative, commercial, and international implications.